Current Treatment Options for Diffuse Purulent Peritonitis - M. R. Garaev; M. A. Nartailakov; V. D. Dorofeev (Креативная хирургия и онкология, 2025)
Introduction. Diffuse purulent peritonitis is considered a prevalent and severe pathological condition in clinical practice. The diagnosis and effective treatment of this condition have been subjects of study for decades, yielding certain advancements. Despite these efforts, mortality rates associated with severe forms remain high, varying considerably from 25–29% to 65%. This review analyzes the five-year experience in treating severe forms of diffuse purulent peritonitis at the G.G. Kuvatov Republican Clinical Hospital (Ufa, Russia), highlighting a broad spectrum of etiological factors and identifying the most significant predictors influencing patient outcomes. Aim. This study aims to examine etiological factors contributing to peritonitis and to identify confounders that increase the risk of adverse outcomes. In addition, we determine optimal surgical strategies tailored to specific disease characteristics. Materials and methods. From 2019 to 2023, a total of 121 patients diagnosed with diffuse purulent peritonitis were treated at Department No. 2 (Department of Purulent Surgery) of the Republican Clinical Hospital named after G.G. Kuvatov. The therapeutic approach was guided by the principles of modern purulent surgery, current National Clinical Recommendations, and individualized patient assessment. Results and discussion.The overall mortality rate was 35.54%. The factors influencing treatment outcomes in patients with peritonitis are critical for determining therapeutic strategies and refining prognostic assessments. The Mannheim peritonitis index (MPI) is widely regarded as a reliable tool for assessing the severity of intra-abdominal inflammation; however, some researchers question its universal applicability. Several alternative methods for evaluating peritonitis severity and prognosis are currently available. Conclusion. Female sex, the presence of malignant neoplasms, complicated colonic pathology, fistulas in the proximal gastrointestinal tract, and laparostomy wounds were among the most unfavorable prognostic factors. The MPI correlates with disease severity, with values exceeding 24 serving as a marker for severe peritonitis. Planned relaparotomies for peritoneal lavage remain a valuable approach in treating patients with diffuse purulent peritonitis. The integration of advanced technologies and methods may contribute to improving treatment outcomes in the future.